Competitive analysis by automotive repair shops, using customer perceived value (2015)
This paper addresses the use of customer perceived value (CPV) as a tool for competitive analysis among automotive repair and maintenance shops. It describes how to determine both the relative importance of properties taken into account by customers when assessing the performance of an automotive repair shop, and the performance assessment conducted by the users of repair shops owned by car dealers and by individuals. Subsequently, it illustrates how both types of repair shops view their competitive position. It also shows the gap between the ideal expected values and the values perceived by the market which becomes a sort of “map” of opportunities both for businesses currently present in the market and for new participants.